Coping Mechanisms of Previously Diagnosed and New HIV-Discordant, Heterosexual Couples Enrolled in a Pilot HIV Self-Testing Intervention Trial in Central Uganda - Matovu, Joseph K. B.; Kisa, Rose; Malek, Angela M.; Vrana-Diaz, Caroline; Mukama, Semei Christopher; Musoke, William; Korte, Jeffrey E.; Wanyenze, Rhoda K. (Frontiers in Reproductive Health, 2021)
Introduction: Learning that a couple has HIV-discordant results can create tensions in the relationship including separation. We explored the coping mechanisms of HIV-discordant, heterosexual couples enrolled in an HIV self-testing (HIVST) intervention trial in Central Uganda. Materials and methods: This qualitative study was nested within a pilot HIVST intervention trial targeting pregnant women and their male partners in central Uganda. In-depth interviews were conducted with 18 individuals from 13 HIV-discordant couples between July and September 2018; 18 months after the end of the main trial. Data were collected on the couples’ initial reactions after learning about their HIV-discordant status, mechanisms adopted by couples to cope with HIV-discordance, and suggestions on how couples in similar situations can be supported. Interviews were transcribed verbatim and analyzed manually following a thematic framework approach. Findings: Of the 13 HIV-discordant couples, seven had the female partner HIV-positive (M-F+) while six had the male partner HIV-positive (F-M+). The mean (±SD) age of the participants was 32.6 (±6.4) years and participants had stayed together for an average of 5.5 (±3.6) years. Fourteen participants from nine couples already knew about their HIV-discordant status by the time they participated in the HIVST trial. After learning about their HIV-discordant status, most individuals (15) thought of abandoning their relationship; three (3) thought of committing suicide. To cope with HIV-discordance, some couples reported that they sought professional counselling support from healthcare providers, and this was particularly true for couples that were already aware of their HIV-discordant status by the time they participated in the HIVST trial. However, new couples that learnt about their HIV-discordant status after participating in the trial reported that they sought psycho-social support from friends or relatives. In the majority of cases, couples reported that they reduced the frequency of sex or abstained from sex; some couples temporarily separated from their partners, while a few others resorted to using condoms to reduce HIV infection risk. Conclusion: Couples used a variety of approaches to cope with HIV-discordance. Study findings underscore the importance of ongoing professional counselling and psycho-social support in helping couples to cope with HIV-discordance.